Inclusion Properties of Orlicz and Weak Orlicz Spaces - Al Azhary Masta; Hendra Gunawan; Wono Setya Budhi (Institute for Research and Community Services (LPPM) ITB, 2016)
This paper discusses the structure of Orlicz spaces and weak Orliczspaces on â„n. We obtain some necessary and sufficient conditions for the inclusion property of these spaces. One of the keys is to compute the norm of the characteristic functions of the balls in â„n.